2016
DOI: 10.1128/aem.01036-16
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress Modulates Mycelium Growth, Heat Shock Protein Expression, Ganoderic Acid Biosynthesis, and Hyphal Branching of Ganoderma lucidum via Cytosolic Ca 2+

Abstract: Heat stress (HS) influences the growth and development of organisms. Thus, a comprehensive understanding of how organisms sense HS and respond to it is required. Ganoderma lucidum, a higher basidiomycete with bioactive secondary metabolites, has become a potential model system due to the complete sequencing of its genome, transgenic systems, and reliable reverse genetic tools. In this study, we found that HS inhibited mycelium growth, reduced hyphal branching, and induced the accumulation of ganoderic acid bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 49 publications
4
90
0
Order By: Relevance
“…S2 and Table S4). In Ganoderma lucidum, heat stress induced a significant increase in the cytosolic Ca 2+ concentration, regulating the accumulation of HSPs and downstream events in filamentous fungi [71]. In plants, it was reported that calcium-activated calmodulin (Ca 2+ -CaM) and calcium-dependent protein kinase (CDPK) were directly involved in the heat stress signal transduction pathway and up-regulated heatshock proteins (HSPs) under heat stress [72][73][74].…”
Section: Signal Transduction In Response To Heat Stressmentioning
confidence: 99%
“…S2 and Table S4). In Ganoderma lucidum, heat stress induced a significant increase in the cytosolic Ca 2+ concentration, regulating the accumulation of HSPs and downstream events in filamentous fungi [71]. In plants, it was reported that calcium-activated calmodulin (Ca 2+ -CaM) and calcium-dependent protein kinase (CDPK) were directly involved in the heat stress signal transduction pathway and up-regulated heatshock proteins (HSPs) under heat stress [72][73][74].…”
Section: Signal Transduction In Response To Heat Stressmentioning
confidence: 99%
“…Previous studies have demonstrated that HS can enhance GA biosynthesis (Zhang et al ., ). To further study the relationship between membrane fluidity and GA biosynthesis, we examined the effect of the membrane fluidizer BA and membrane rigidifier DMSO, which are used to increase and decrease the lipid bilayer's membrane fluidity, respectively (Suri and Dhindsa, ; Saidi et al ., ), during GA biosynthesis.…”
Section: Resultsmentioning
confidence: 97%
“…As shown in Fig. B, HS‐treated‐only strains led to an increase ( P < 0.05) of approximately 1.7‐fold in the GA content compared with the non‐HS treatment, which was consistent with previous reports ( Z hang et al ., ). The addition of different concentrations of DMSO alleviated this increase.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations